Response of Pakcoy Plant Growth and Production to the Application of Poc and Manure - Panataria, Lince Romauli; Simanjuntak, Pantas; Sitorus, Efbertias; Saragih, Meylin Kristina; Manurung, Agnes Imelda (ITScience (Information Technology and Science), 2024)
Pakcoy (Brassica rapa L.) is a type of vegetable plant is used by people in various dishes because it contains minerals, protein, Vitamin A, Vitamin B, Vitamin B2, Vitamin B6, Vitamin C, potassium, phosphorus, copper, magnesium, iron, carbohydrates and fiber.This research aims to see the effect of giving POC and chicken manure on the growth and production of pakcoy plants. This research was carried out using a factorial Randomized Block Design (RAK) which consisted of two factors, namely the concentration of chicken manure which consisted of 3 levels, namely A0 = 0 kg / plot, A1 = 1 kg / plot, A2 = 2 kg / plot, and A3 = 3 kg / plot. The second factor is the POC dose which consists of 4 levels, namely. E1=10 ml/liter water/m2, E2= 20 ml/liter water/m2 and E3=30 ml/liter water/m2. The results showed that the application of chicken manure had no significant effect on the number of leaves, wet harvest weight per plot, wet harvest weight per hectare, wet sale weight per hectare. The interaction between giving chicken manure and POC had a significant effect on the number of leaves, wet weight of harvest per plot, wet weight of harvest per hectare, wet weight of sale per hectare.